Alternative splicing generates messages encoding rat c-erbA proteins that do not bind thyroid hormone. - Mitsuhashi, T (1988)
The nucleotide and predicted amino acid sequences of two variant cDNAs [rat brain thyroid hormone receptor (rTR alpha) vI and vII], isolated from a rat brain cDNA library by using the Pst I fragment of v-erbA, showed virtual identity with the rat brain thyroid hormone receptor (rTR alpha) [Thompson, C. C., Weinberger, C., Lebo, R. & Evans, R. M. (1987) Science 237, 1610-1614] in the putative DNA binding domain and in the first 180 amino acids of the hormone binding domain but no similarity except for 5 amino acids at the extreme 3' end. Isolation and sequencing of the 3' end of the gene coding for rTR alpha, vI and vII mRNAs revealed that the 3' heterogeneity is due to alternative splicing of the primary transcripts of the same gene. RNA transfer blot analyses with probes unique to rTR alpha, rTR alpha vI, and rTR alpha vII showed that only the variant mRNAs are abundantly expressed in rat brain, contrary to the previously reported high-level expression of rTR alpha. Since in vitro translation products of rTR alpha vI and rTR alpha vII did not bind thyroid hormones specifically, our findings explain the discrepancy between the reported abundance of the receptor mRNA and the low receptor levels determined by ligand binding studies in rat brain. These variant mRNAs are also expressed in kidney, heart, spleen, and liver, albeit at lower levels. The presence of an intact DNA binding domain in rTR alpha vI and rTR alpha vII suggests that the variants might have modulating functions in thyroid hormone action.